Self-Concept, Achievement Goals and Bullying in Physical Education - Liakou Ευαγγελία; Digelidis Νικόλαος; Chatzigeorgiadis Αντώνης; Papaioannou Αθανάσιος (Inquiries in Physical Education and Sport, 2010)
The aim of this study was to examine bullying behaviours in Greek P.E. and the relations between bullying and victimization with self-concept, goals orientations and motivational climate as well as the differences in bullying and victimization behaviours among the two genders. In the first survey 100 students participated (52 boys, 48 girls), aged 11-12 years (5th and 6th graders). They had to respond in 12 items about the frequency of bullying behaviours in PE. The results showed that the higher scores (above average) were evident in the following items: i) “some children are always teased by other students” and ii) “some children are being fooled by other students”. In the 2nd survey 290 students (147 boys, 143 girls) participated, aged 11-12 years (5th and 6th graders). The results from correlational analysis showed that victimization and bullying were of medium positive correlation. Moreover, victimization was positively connected with ego-protecting goal and perceived teacher’s emphasis on ego-protection and negatively with perceived teacher’s emphasis on personal progress and general self- concept , whereas bullying was connected positively the with ego-enhancing and ego-protecting goals, with the perceived teacher’s emphasis on ego – enhancement , perceived teacher’s emphasis on ego- protection and negatively with the perceived teacher’s emphasis on personal progress and general self- concept. Additionally, analysis of variance indicated that boys higher bullying scores than girls. In conclusion, it’s obvious that the P.E. teacher may play a role as far as preventing undesirable behaviours as teacher’s emphasis on personal progress may decrease bullying and victimization behaviours.